The influence of subclinical mastitis on the protein composition and protease activities of raw milk from lactating Thai-crossbred dairy cows - Attapol Tiantong; Sirichai Eardmusic; Pipat Arunvipas; Jai-Wei Lee; Wilasinee Inyawilert (Veterinary World, 2023)
Background and Aim: Mastitis in dairy cattle is associated with a high rate of morbidity and death, which has major implications for milk production and quality. This study aimed to investigate the protein component and the activity of matrix metalloproteinase-2 (MMP-2) and -9 (MMP-9) in raw milk samples with different testing scores determined using the California mastitis test (CMT).